Automatic personalized student timetable / Siti Aishah Mohamed Amin - Mohamed Amin, Siti Aishah (2010)
Time tabling is one of the most important administrative activities that take place in academic institutions. Timetable Scheduling takes a huge effort at the beginning of each year or semester for every university program. A large number of variants of the timetabling problem have been proposed in the literature, which differ from each other based on the type of institution involved, university or school, and the type of constraints. Inthis paper, I have resolved the problem of timetable scheduling using Genetic Algorithm.